Spontaneous Uterine Rupture During Pregnancy: Does Previous Uterine Septum Resection Trigger It? - Kübra Boynukalın; Melih Velipaşaoğlu; İbrahim Esinler (Medical Network, 2008)
Even though uterine rupture during pregnancy following a hysteroscopic septum resection is a very infrequent complication, patients contemplating pregnancy after this procedure complicated by perforation should be aware of potential risk of uterine rupture.